Complete chloroplast genome sequence of Michelia champaca var. champaca Linnaeus, an ornamental tree species of Magnoliaceae - Shaoyu Chen; Tao Wu; Yupin Fu; Jiabo Hao; Huifen Ma; Yunfeng Zhu; Yongkang Sima (Mitochondrial DNA. Part B. Resources, 2020)
Michelia champaca var. champaca is an ornamentally important tree in Magnoliaceae. The paper reported the complete chloroplast genome (cpDNA) of M. champaca var. champaca and its basic annotated information. The size of cpDNA is 160,008 bp, with a typical quadripartite structure of a large single-copy (LSC) region of 88,037 bp and a small single-copy (SSC) region of 18,809 bp separated by a pair identical inverted repeat regions (IRs) of 26,581 bp each. The genome contained 131 genes (113 unique), including 86 protein-coding genes (80 unique), 37 tRNA genes (29 unique), and eight rRNA genes (four unique). Phylogenetic analysis showed that M. champaca var. champaca is affinal to M. baillonii and they form a nomophyletic group with other eight Michelia species. This Michelia clade is sister to the Aromadendron cathcartii clade with high support. All genera mentioned in this analysis are nomophyletic under the system of Magnoliaceae by Sima and Lu.